In the people's court ; Children betrayed ; Reflections of Larry Alcala [videorecording] - Lazaro, Cheche (Quezon City Probe Productions, 1995)
The trial of Hubert Webb is a much waited event. Pedophiles continue and the victims are street children. Interview with Larry Alcala in cartooning.
In the people's court (15 min.) -- Children betrayed (14 min.) -- Reflections of Larry Alcala (11 min.)
VHS.
Keywords: Alcala, Larry; Vizconde massacre -- 1991. -- Philippines; Cartoonists -- Philippines; Child prostitution -- Philippines; Pedophilia -- Philippines